O espaço prisional como território de auto-organização das mulheres encarceradas na penitenciária feminina de Cajazeiras, Paraíba - Feitosa, Andreia Ceballos (2023)
The mass imprisonment of people, especially women, results in a specific incarcerated profile that evidences social, economic and racial inequality from the penal selectivity. We observed that they are, mostly, black or brown single mothers with low educational levels. In this circumstances, this dissertation aims to analyze the prison space and the women‘s self-organizing strategies inside the female prison system at the city of Cajazeiras/PB. The study starts from a geographical perspective and interdisciplinary contribution according to Santos (1986) and Morin (2003). Based on the attention given to women imprisonment we could lean over other knowledge areas considering the approach of the following authors: Akotirene (2020), Borges (2019), Davis (2016, 2018), Diniz (2015), Foucault (2011), Goffman (1961, 2006), Queiroz (2015). Also authors that deal with the correlation between imprisonment and territory, such as Almeida (2014), Andrade (1995), Arruda (2006, 2015), Haesbaert (2005), Raffestin (1993) and Souza (1995, 2015). We carried out bibliographical research at public domains such as Capes, Redalyc and at Geography, Human Rights, Psychology, Sociology and Social Services graduate programs. We rely our research on treaties and legal provisions such as the 1940‘s brazilian Penal Code, the Decree-law nº 2.848/40, the Penal Execution Law nº 7.210/1984, the Law nº 11.343/2006 (known as the ―anti-drugs‖ law), the Penitentiary Information survey - Infopen Mulheres (2018) and the Bangkok Rules (2016). We performed our field works considering authors as Alentejano and Rocha-Leão (2006), Kaiser (2006) and Marcos (2006), aiming to characterize the profile of the local incarcerated woman. The registration is recorded on a field notebook, photographs and audio files of focal group gathering and individual interviews with the women. We consider that women are historically penalized, the few and recent legislations about the prison environment for women are not enough to ensure establishments that respect human dignity. Although Brazil is building regulations and signing international law agreements, such as Bangkok Rules (2016), the practice is still unhealthy, harmful and hostile. The reflection of the legal and penal system is selective and punitive, as the imprisoned women are frequently arrested for drug trafficking related crimes, whereas in many situations they were led to the practice because of the lack of access to public policies that could guarantee better living conditions. The narratives denote that the deterritorialization of these women caused the breaking of emotional bonds with their families and, under extreme subalternity conditions, it was necessary to create survival strategies under the limits imposed by prison conditions. Although solidarity practices are carried out to maintain a kinder kind of conviviality, the prison is a tactic of social exclusion and degradation of bodies that often need to be docile in order to survive.